KETERAMPILAN INTERPERSONAL DALAM CINTA: KOMUNIKASI EFEKTIF MEMBANGUN HUBUNGAN YANG SEHAT - Adinda Putri Dewi; Wanda Fitri Berliana, Ira Dinanti Hariyanto, Sulistiasih (Jurnal Salome : Multidisipliner Keilmuan, 2024)
Building and maintaining a healthy love relationship is everyone's dream. However, amidst the busyness and complexity of modern life, this is not always easy. Interpersonal skills play an important role in human life, especially in the context of love relationships. Effective communication is considered one of the main components in building and maintaining healthy relationships. However, many relationships or couples still experience difficulties in communicating, causing conflict and dissatisfaction in the relationship. This research was created to determine the importance of effective communication skills in love relationships and their impact on relationship health. The main aim of this research is to explore how interpersonal skills, identifying various factors that can influence the quality of communication in love relationships, especially effective communication, can contribute to the formation and maintenance of healthy love relationships. This research uses qualitative methods by collecting data from relevant sources through literature searches in academic databases and digital libraries. The goal is to gain a deep understanding of individuals' experiences and how they build effective communication in their relationships. Research results show that couples who have good communication skills tend to have more harmonious and satisfying relationships. Through open, honest and empathetic communication, couples can understand each other, respect, respect, support each other, and resolve conflicts constructively. This creates strong bonds and strengthens emotional involvement between family, partners, friends and the surrounding environment. The conclusions of this study confirm that effective communication and the development of good interpersonal skills are key in building and maintaining healthy love relationships.